Map of the State of Maryland laid down from an actual survey of all the principal waters, public roads, and divisions of the counties therein; describing the situation of the cities, towns, villages, houses of worship and other public buildings, furnaces, forges, mills, and other remarkable places; and of the Federal Territory - John Vallance (J. Vallance, 1795)
Includes "Plan of the city of Washington and Territory of Columbia" and a dedication. Full map available online through the Library of Congress Web site (https://www.loc.gov/resource/g3840.ct000307/)